Average Resonance Parameters of Tellurium and Neodymium Nuclei - Pravdivy, M.M.; Korzh, I.O.; Sklyar, M.T. (Ukrainian Journal of Physics, 2012)
Complete sets of average resonance parametersS0, S1, R’0, R’1, and S1,3/2 for tellurium and neodymium nuclei with natural isotope contents have been determined by analyzing the experimental differential cross-sections of neutron elastic scattering in the energy range lower than 440 keV. The data obtained, the recommended parameter values, and some literature data have been analyzed.